(3fgGjI GdHjGf aj OQGjI GdReGfs - (3GdbjUQj, GdbQGeGfj, OGhO Hf eMehO Hf eMeO (B751 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B...(3GdMeO ddg GdChd hGdBNQ(B...(3hHYO jbhd GdYHO GdVYja(B...(3OGhO Hf eMehO(B...(3deG CjOfj GdJhajb HJMUjd Ydhe GdMbGFb hGdObGFb(B...(3hcGf CTQa GdYdhe hCYdGgG QJHI hCcedgG hCLdgG TCfG hefRdI dCf ehVhYgG GdPGJ GdEdGgjI(B...s
(3BNQgG (B:s
...(3ceG bGd Gddg (B-(3JYGdi(B- {(3bd Ef GdChdjf hGdBNQjf deLehYhf Edi ejbGJ jhe eYdhe(B} ...(3eG hLO ecJhHG aj bHQ(B...(3ajchf eOI(B...(3GKfi YTQ Cda SfI(B...(3Je GdQSGdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B1(3,U(B702s
(3cTa GdXfhf(B:(3L(B2(3,U(B1987s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds